James C. VanderKam, The Dead Sea Scrolls and the Bible, Grand Rapids, Michigan/ Cambridge, UK, Eerdmans, 2012, 202pp ISBN 978-0802866790, USD 25. - Gardner, Anne E. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
None